Reproducibility Trials in a Research Brewery and Effects on the Evaluation of Hop Substances in Beer: Part 3: Transfer Rates of Aroma Compounds from Hops to Beer and their Ageing Behaviour - Gahr, Andreas; Forster, Adrian; De Clippeleer, Jessika; Van Opstaele, Filip (BrewingScience, 2019)
The reproducibility aspect of fresh and moderately aged late and dry hopped beers was previously reported in the papers part 1 [1] and part 2 [2] respectively. The present paper (part 3) focuses on the transfer of several compounds from hops to beer and their behaviour during beer ageing at different temperatures for 470 days. Transfer rates were found to be different for the examined substance groups and whether the hops were applied in the brewhouse (late) or during maturation (dry hopped): mono- and sesquiterpene hydrocarbons